Neuropsychological Intervention Using an Islamic Religious Approach to Prevent Bullying: Case Study at Madrasah Aliyah Mu'allimaat Muhammadiyah Yogyakarta - Us'an, Us'an; Suyadi, Suyadi; Siraj, Saedah Binti (Universitas Muhammadiyah Magelang, 2023)
Bullying cases continuously spread in educational institutions so that they affect student physical and psychological development and even give the institution reputation bad name. Madrasah Mu’allimaat Muhammadiyah Yogyakarta, on the other hand, is able to decrease the number of bullying cases. The objective of this research is to theorize bullying preventing practices in Madrasah Muallimaat Muhammadiyah Yogyakarta. The approach of this research is descriptive qualitative. The informants of the research are the head of the madrasah, teachers, and students. The data collection methods are observation, interview, interpretation, and documentation. The data analyses are done with description, categorization, interpretation, and theorization. The result of the research shows that bullying preventing practices are done by combining psychological approach, neuroscience, and Islamic learning. The practices are then theorized into neuropsychology. Neuropsychology learns the relationship between brain and behavior, studies various functions including knowledge, skills in managing emotions focusing on empowering individuals. Neuropsychological interventions done at Madrasah Muallimaat Yogyakarta are: (1) Self-control through guidance, (2) Self-control through fasting habitation, (3) Self-control through collaboration and the values of friendship, (4) Self-control through religious activities (5) Self-control through empathy among students, and (6) self-control through patience and discipline. Theoretical configuration of the neuro-psycholgical intervention can be a model for the next research on bullying prevention in other Islamic educational institutions.